2020
DOI: 10.1021/acsami.0c07075
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry-Controlled MoxW1–xTe2 Nanowhiskers: A Novel Electrocatalyst for Pt-Free Dye-Sensitized Solar Cells

Abstract: Novel polymorphic Mo x W1–x Te2-based counter electrodes possess high carrier mobility, phase-dependent lattice distortion, and surface charge density wave to boost the charge-transfer kinetics and electrocatalytic activity in dye-sensitized solar cells (DSSCs). Here, we report the syntheses of stoichiometry-controlled binary and ternary Mo x W1–x Te2 nanowhiskers directly on carbon cloth (CC), denoted by Mo x W1–x Te2/CC, with an atmospheric chemical vapor deposition technique. The synthesized Mo x W1–x Te2/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“… 32 Moreover, thin-film growth technology is a highly automated process, and thus, it could warrant the quality and reliability of electrolyzer devices based on metallic 1T′-MoTe 2 thin films compared with sprayed interfaces. Recent successes in fabrication of 1T′-MoTe 2 films on CC 33 , 34 demonstrated that large film areas (imperative for electrolyzer applications) are achievable. This enables a pivotal shift to rigorous evaluation of the films in industrially relevant full-scale flow-cell PEM electrolyzers.…”
Section: Introductionmentioning
confidence: 99%
“… 32 Moreover, thin-film growth technology is a highly automated process, and thus, it could warrant the quality and reliability of electrolyzer devices based on metallic 1T′-MoTe 2 thin films compared with sprayed interfaces. Recent successes in fabrication of 1T′-MoTe 2 films on CC 33 , 34 demonstrated that large film areas (imperative for electrolyzer applications) are achievable. This enables a pivotal shift to rigorous evaluation of the films in industrially relevant full-scale flow-cell PEM electrolyzers.…”
Section: Introductionmentioning
confidence: 99%
“…In DSSCs, TMD-based electrocatalysts play a crucial role in facilitating redox reactions. It has been observed that maintaining a consistent supply of electrons on the surface of TMDs can greatly enhance their electrochemical activity [25].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In addition, it has received considerable attention owing to its straightforward design and affordable price. 8,9 In general, photoanode, counter electrode (CE), and electrolyte are the three main components in DSSCs, of which CE is mainly used to collect and transfer external circuits, thus catalyzing the reduction of I 3 − on the interface between CE and electrolyte. [10][11][12] Commercially, Pt is generally considered the benchmark for CE, but the high cost and lack of availability restrict its wide usage.…”
Section: Introductionmentioning
confidence: 99%